IMPROVING SOCIAL STUDIES LEARNING IN ELEMENTARY SCHOOLS: A LITERATURE STUDY - Fauzi, Zain Ahmad; Ayuni, Helwa (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2024)
Social Studies (IPS) in Elementary Schools (SD) shapes students' understanding of the social and cultural environment. However, IPS learning in elementary schools often faces problems, including overly theoretical teaching methods, lack of technology, materials irrelevant to students' lives, limited teacher professional development, and an evaluation system focusing on memorization. This article uses a literature study method to identify these problems and offers relevant solutions. The study results indicate that implementing Project-Based Learning (PBL), integrating technology, adopting contextual approaches, providing teacher professional development, and utilizing authentic assessments can improve the effectiveness of IPS learning. By implementing these solutions, it is hoped that IPS learning in elementary schools will be more interactive, engaging, and able to equip students with the critical thinking skills needed to face future social challenges.